PEMBERDAYAAN LMDH BUMI LESTARI MULYOREJO PRIGEN PASURUAN MELALUI PELATIHAN PENGOLAHAN MINUMAN HERBAL INSTAN DAN MANISAN HERBAL BERBASIS KEARIFAN LOKAL - Ainiyah, Roisatul; Utami, Cahyaning Rini; Rismawati, Senja Ike (Jurnal Abdi Insani, 2025)
The Lembaga Masyarakat Desa Hutan (LMDH) Bumi Lestari in Prigen, Pasuruan manages the Sapen Forest with more than 70 potential medicinal plant species, yet their use remains limited to traditional consumption and has not produced market-ready products. This condition highlights the need for community empowerment through training in processing local medicinal plants into practical products. The aim of this activity was to improve community skills in processing ginger into instant herbal drinks and herbal candied products that are hygienic, high quality, and marketable. The method applied a participatory approach consisting of situation analysis, socialization, technical training based on learning by doing, mentoring, and evaluation using pre–posttest questionnaires analyzed with the Wilcoxon test. The results showed a significant improvement of 31.4%, with average scores increasing from 55.3 (pre-test) to 86.7 (post-test) (p<0.05). Participants were able to apply proper processing steps, from raw material preparation, production, to packaging and labeling of products. Sensory evaluation indicated good acceptance, although adjustments were still needed in sugar concentration and boiling duration to reduce pungency in ginger candy. The training successfully empowered LMDH Bumi Lestari members to produce marketable herbal products based on local wisdom. Keywords: community empowerment, instant herbal drink, herbal candy, ginger, local wisdom